PEMODELAN DISPERSI POLUSI UDARA DARI AKTIVITAS PLTU CIREBON PADA MUSIM KEMARAU DAN HUJAN SERTA PENGGUNAAN 2 CEROBONG ASAP - , MUHAIMIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis examines the predictive distribution of air pollutants (SOx, NOx, CO and total particles) emitted from the power plant at Cirebon area activities. Gaussian model and some scenarios used to predict the concentration of pollutant gases. The purposes of this study were to determine the distribution of the flue gas from the power plant activity, determine the difference pollutant gas concentrations in the wet and dry seasons, modeling the use of a power plant stack with 2 stacks, and estimate the ambient air quality as a result of air pollution ditumbulkan of activities of the power plant activities. The results showed that modeling with gaussian plume models can be used to predict the dispersion of pollutants in the air as well.. The maximum concentration is lower in the wet season is lower than in the dry season. The maximum concentration in the wet season was 30.14 Î¼g/m3 for SOx, 26.35 Î¼g/m3 for NOx, 0.79 Î¼g/m3 for CO and 0.45 Î¼g/m3 for total particles. While in the dry season, the maximum concentration was 42.38 mg/m3 for SOx, 34.78 Î¼g/m3 for NOx, 0.96 Î¼g/m3 for CO and 0.70 Î¼g/m3 for total particles. The maximum concentration that results from modeling by using 2 stacks were 51.49 Î¼g/m3 (stacks with a sideways position) and 52.95 Î¼g/m3 (with a stack-to-back position). This concentration is higher than the model by using 1 stack of 36.89 Î¼g/m3. Ambient air quality for pollutants shows still under ambient air quality standards based on PP 41 1999. Keywords: gaussian model, power plants, air pollution, stack